2016
DOI: 10.1155/2016/1739760
|View full text |Cite
|
Sign up to set email alerts
|

Hataedock Treatment Has Preventive Therapeutic Effects in Atopic Dermatitis‐Induced NC/Nga Mice under High‐Fat Diet Conditions

Abstract: This study investigated the preventive therapeutic effects of Hataedock (HTD) treatment on inflammatory regulation and skin protection in AD-induced NC/Nga mice under high-fat diet conditions. Before inducing AD, the extract of Coptidis Rhizoma and Glycyrrhiza uralensis was administered orally to the 3-week-old mice. After that, AD-like skin lesions were induced by applying DNFB. All groups except the control group were fed a high-fat diet freely. We identified the effects of HTD on morphological changes, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
1
7
0
1
Order By: Relevance
“…In Korean medicine, Hataedock (HTD), herbal extracts that are orally administered to neonates and infants, was used to clear fetal heat to prevent inflammatory diseases. Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 51%
“…In Korean medicine, Hataedock (HTD), herbal extracts that are orally administered to neonates and infants, was used to clear fetal heat to prevent inflammatory diseases. Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 51%
“…In AD, NO, iNOS and COX-2 stimulated by TNF-α/IFN-γ and IL-1β contributed to induce AD ( Orita et al ., 2011 ; Ahn et al ., 2016 ). Some studies such as Hataedock, Quercetin, Resveratrol and K112PC-5 show that anti-AD effects via inhibition of NO production, iNOS, COX-2 and cytokines ( Kang et al ., 2008 ; Karuppagounder et al ., 2014 , 2015; Cha et al ., 2016 ). Our study indicated that carnosol has anti-AD effect through reducing inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports in literature investigated the anti-inflammatory effects of Actinidia arguta (hardy kiwi) [50,51]. Chinese herbs, such as Rhemannia glutinosa, Paeonia lactiflora, and Glycyrrhiza uralensis have a significant steroid sparing effect when administered in combination with methylprednisolone for the management of canine AD, in addition to having inflammatory, antioxidant, and antimicrobial properties [52][53][54][55][56][57][58][59][60][61]. Arctium lappa, Althaea officinalis, Malva sylvestris, and Ribes nigrum also are attributed with antioxidant and anti-inflammatory activities [62].…”
Section: Botanical Extractsmentioning
confidence: 99%